2013
DOI: 10.1371/journal.pone.0060799
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Diet of Elusive Rainforest Herbivores in Next Generation Sequencing Era? The Tapir as a Case Study

Abstract: Characterizing the trophic relationships between large herbivores and the outstanding plant diversity in rainforest is a major challenge because of their elusiveness. This is crucial to understand the role of these herbivores in the functioning of the rainforest ecosystems. We tested a non-invasive approach based on the high-throughput sequencing of environmental samples using small plant plastid sequences (the trnL P6 loop) and ribosomal ITS1 primers, referred to as DNA metabarcoding, to investigate the diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 54 publications
0
68
0
Order By: Relevance
“…Several of the soil-based DNA metabarcoding studies targeted earthworms (Bienert et al 2012;Ficotela et al 2015;Pansu et al 2015a) or large vertebrates . Gut and faecal material, collected in 5% of the studies, has been used to analyse the diets of herbivores (Hibert et al 2013), carnivores and carrion feeders (Calvignac-Spencer et al 2013). Several of the 167 DNA metabarcoding studies analysed pools of invertebrate specimens collected in malaise traps (Yu et al 2012;Ji et al 2013;Liu et al 2013;Yang et al 2014) or from soil samples , while others targeted invertebrate DNA extracted directly from soil (McGee & Eaton 2015) or aquatic habitats (Pochon et al 2013;Cowart et al 2015).…”
Section: Study Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the soil-based DNA metabarcoding studies targeted earthworms (Bienert et al 2012;Ficotela et al 2015;Pansu et al 2015a) or large vertebrates . Gut and faecal material, collected in 5% of the studies, has been used to analyse the diets of herbivores (Hibert et al 2013), carnivores and carrion feeders (Calvignac-Spencer et al 2013). Several of the 167 DNA metabarcoding studies analysed pools of invertebrate specimens collected in malaise traps (Yu et al 2012;Ji et al 2013;Liu et al 2013;Yang et al 2014) or from soil samples , while others targeted invertebrate DNA extracted directly from soil (McGee & Eaton 2015) or aquatic habitats (Pochon et al 2013;Cowart et al 2015).…”
Section: Study Environmentsmentioning
confidence: 99%
“…A majority of studies of plant DNA were based on the trnL UAA intron within the chloroplast transfer RNA, or tRNA gene (e.g. Hibert et al 2013;Parducci et al 2013;Pedersen et al 2013). The DNA of arthropods was most commonly targeted by amplification of mitochondrial cytochrome c oxidase subunit I (COI) DNA (e.g.…”
Section: Summary Of Gene Regions Used In Prior Analyses Of Environmenmentioning
confidence: 99%
“…8 using gut or faecal DNA in parasites (Schnell et al, 2012), herbivores (Hibert et al, 2013) or detritivores (Calvignac-Spencer et al, 2013b), the estimation of abundance is much more difficult in these cases because many individuals often feed on the same individual prey (or host) without necessarily causing its death. This means that although presence or absence of the prey (or host) species can be accurately estimated (Calvignac-Spencer et al, 2013a), the occurrence of prey DNA in the faeces of parasites, herbivores or detritivores (i.e.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Annotated sections were then removed, leaving only the ITS2 sequence. Contigs with a read depth of less than 10 were excluded in both genes in the main analysis, following the 10-minimum read depth protocol of Hibert et al (2013) and Gebremedhin et al (2016). We also carried out a supplementary analysis with all the same conditions but at a minimum read depth of 3.…”
Section: Hts Data Analysismentioning
confidence: 99%
“…These new methods have been found to recover greater diversity in faecal samples than traditional ones (Soininen et al 2009). Most studies of diet from faecal material have focused on carnivores , Shehzad et al 2012, however, several studies have shown that the technique can work in herbivores (Soininen et al 2009, Hibert et al 2013, Symondson and Harwood 2014. In this study, we use faecal DNA barcoding analysis to characterize the diets of economically and ecologically significant Dorper and Merino sheep (Ovis aries) and the goat (Capra aegagrus hircus).…”
Section: Introductionmentioning
confidence: 99%